2012
DOI: 10.1038/nature11519
|View full text |Cite
|
Sign up to set email alerts
|

Increased HIV-1 vaccine efficacy against viruses with genetic signatures in Env V2

Abstract: SummaryThe RV144 trial demonstrated 31% vaccine efficacy (VE) at preventing HIV-1 infection1. Antibodies against the HIV-1 envelope variable loops 1 and 2 (V1/V2) domain correlated inversely with infection risk2. We hypothesized that vaccine-induced immune responses against V1/V2 would selectively impact, or sieve, HIV-1 breakthrough viruses. 936 HIV-1 genome sequences from 44 vaccine and 66 placebo recipients were examined. We show that vaccine-induced immune responses were associated with two signatures in V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
460
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 399 publications
(475 citation statements)
references
References 30 publications
14
460
0
1
Order By: Relevance
“…Because this approach to assess the impact of the vaccine from the viewpoint of viruses penetrating injury, because they represent the other side of the coin of the associated immune response. The sieve analysis was conducted targeting viruses penetrate RV144 found that the vaccine-induced differential gain of HIV-1 on the basis of viral sequences in the region that V2 [80]. These data support the hypothesis that linked the responses V1/V2 with the protection of the vaccine-induced.…”
Section: Step Studysupporting
confidence: 72%
See 1 more Smart Citation
“…Because this approach to assess the impact of the vaccine from the viewpoint of viruses penetrating injury, because they represent the other side of the coin of the associated immune response. The sieve analysis was conducted targeting viruses penetrate RV144 found that the vaccine-induced differential gain of HIV-1 on the basis of viral sequences in the region that V2 [80]. These data support the hypothesis that linked the responses V1/V2 with the protection of the vaccine-induced.…”
Section: Step Studysupporting
confidence: 72%
“…Investigators are also under study of the function of bNAbs and their development during the HIV-I infection. As a result, many bNAbs have been isolated from the patients who are chronically infected by HIV and also been under detailed study [80][81][82][83][84][85][86][87][88][89][90][91]. Although antigens which are performing the reaction of these antibodies have not been yet identified.…”
Section: Developmental Study Of Hiv Vaccinementioning
confidence: 99%
“…In outcomes like these, where protection is incomplete, the characterization of breakthrough variants can inform us about correlates of vaccine-mediated protection against acquisition (18,22,23). Here, we went one step further by testing the capacity of prechallenge antibodies to neutralize the exact Env variant that broke through to establish each infection.…”
mentioning
confidence: 99%
“…IgG antibodies specific to the V1/V2 region of HIV-1 gp120 correlated with a decreased risk of infection with evidence of a virus sieve effect in infected vaccine recipients at this gp120 region [72,73]. Although the exact mechanism mediating protection by these antibodies in the trial is not yet known, they are thought to block T-cell associated integrin, a4b7, which is involved in HIV-1 entry in activated CD4+ T-cells [74,75].…”
Section: Type Of Immune Responsementioning
confidence: 99%